Formation of the Che River Basin Committee - Sethaputra, Sacha; Sawaengpet, Juljit (Engineering and Applied Science Research, 2013)
This paper summarizes formation of the Che river basin committee. The summary is extracted from a process documentation where a researcher is assigned to record every related events. Basically. The Che river basin committee was formed to facilitate exchange of ideas, arguments and joint decision making among representatives of stakeholders. The goal is to create Integrated Water Resources Management (IWRM) practice in the basin. Apart from rush and lacks of readiness (and similar to other river basin committees in Thailand) there is yet no law supporting the role of the committee. Such shortcomings are detrimental to the committee’s operation. However, formation of lower part expand both in areas, frequency and numbers of affected stakeholders.